A Single‐Point Method to Quantitatively Diagnose the Magnetotail Flapping Motion. Issue 2 (7th February 2021) - Rong, Z. J.; Zhang, C.; Klinger, Lucy; Shen, C.; Cui, J.; Zhang, Y. C.; Wei, Y.
Abstract: Quantitatively estimating magnetotail flapping motion is critical for understanding and characterizing its dynamical behaviors. Such estimation can be achieved in principle by the multipoint analysis of spacecraft tetrahedron, for example, Cluster or MMS mission, but, owing to the inability of single‐point measurement to separate the spatial‐temporal variation of magnetic field, would be inadequate for a single spacecraft. Since single‐point missions dominate explorations of planetary magnetotail, we have developed a single‐point method based on the magnetic field measurement that quantitatively estimates the parameters of flapping motion, including spatial amplitude, wavelength, and propagation velocity. By comparing several applied cases with the multipoint analysis of Cluster, we demonstrate that our method can be reasonably applied to infer the average parameters over the whole flapping period when magnetotail is during quiet phase (magnetic field in magnetotail does not experience significant temporal variation). Thus, this method could be applied widely to the "big data set" accumulated by single‐point spacecraft missions in order to study magnetotail flapping dynamics. Plain Language Summary: The oscillation of a magnetotail current sheet, known as the magnetotail flapping motion, plays an important role in dissipating the magnetic field energy stored in a magnetotail. This flapping motion is a common dynamic behavior of a magnetotail, which has been observed widely for Earth and other planets of our solar system. The comparative study of the planetary magnetotail flapping motion is essential to understand the flapping mechanism. Unfortunately, single‐point measurement of planetary spacecraft does not allow for calculating the flapping velocity of tail current sheet directly, which greatly constrains the lucubration of flapping dynamics. To overcome this difficulty, we present a new single‐point method, based on the magnetic field measurement and reasonable assumptions, to quantitatively estimate flapping parameters such as spatial amplitude, wavelength, and propagation velocity. A comparison with the multipoint analysis of Cluster tetrahedron shows the validity and reliability of our single‐point method as applied to several flapping cases of Earth's magnetotail. Thus, our method could be broadly applied to the "big data set" accumulated by single‐point spacecraft missions in history in order to study the flapping dynamics of planetary magnetotails. Key Points: A single‐point method based on magnetic field measurement is developed to quantitatively diagnose the magnetotail flapping motion The method could be performed better to a local flapping current sheet when magnetotail is during quiet phase Application demonstrates that this method can reasonably infer the average flapping parameters during the whole flapping period